The Transformation of Radical Movement in Yogyakarta post-2019 Presidential Election - Hergianasari, Putri; Netanyahu, Kurniawan (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2021)
Radical movements colored the 2019 Elections, especially the dichotomy of the Jokowi and Prabowo camps. This phenomenon also occurs among the people of Yogyakarta after the 2019 Presidential Election. The research aims to map the transformation of fundamentalist groups in Yogyakarta after the 2019 Presidential Election. The significant analysis was carried out to provide sources of information to the public and government regarding the transformation of Hizbut Tahrir Indonesia (HTI) after the 2019 Presidential Election. The researchers used qualitative descriptive methods with the analysis of the theory of social resource mobilization. The research results showed that the transformation of the radical movement that formerly took the anarchist forms and down to the streets, now is more focused and organized by entering the community through religious education and recitation groups, both in universities and at household meetings. This research concludes that in order not to be parallel to HTI, which the government dissolved, the transformation of tranquility is one way to maintain the existence of radical organizations but in a more friendly framework or guise. All of these resource mobilization movements take the form of informal social networks.